Factors affecting the efficacy and safety of aminophylline in treatment of apnea of prematurity in neonatal intensive care unit - Chaohui Ye; Caiyun Miao; Li Yu; Zhuoya Dong; Jie Zhang; Yingying Mao; Xiaodong Lu; Qin Lyu (Pediatrics and Neonatology)
Background: The factors affecting the safety and efficacy of aminophylline use in the treatment of apnea of prematurity (AOP) in the neonatal intensive care unit (NICU) are not clear. In this study, we aimed to evaluate the potential factors affecting the efficacy and safety of aminophylline in AOP treatment at standard doses and to determine appropriate patients for this therapy. Methods: Over a 3-year period (January 2012 to December 2014), the medical records of 206 preterm infants with apnea who were admitted to the NICU of our hospital to receive aminophylline infusions were retrospectively reviewed. These infants were subjected to routine theophylline monitoring by reversed-phase high performance liquid chromatography. The primary outcome measures were the efficacy of aminophylline treatment and adverse reactions observed upon administration. Results: One-hundred and twenty-seven (61.65%) infants were considered to have undergone effective therapy and classified accordingly. Gestational age, body weight at the initiation of aminophylline, and serum theophylline concentration were identified as protective factors of therapeutic efficacy. Receiver operating characteristic (ROC) analysis indicated cutoff values of 30.36 weeks for gestational age and 1.69 kg for body weight at initiation of aminophylline administration for ensuring high efficacy of aminophylline for AOP. Fifty-three (25.73%) infants had adverse reactions. Birth weight and serum concentration of theophylline were associated with an increased risk of adverse reactions, with odds ratios of 0.167 and 1.346, respectively. The ROC curves indicated a birth weight cutoff value of 1.48 kg. Conclusion: Infants with apnea and gestational age >30.36 weeks, body weight at initiation of aminophylline treatment above 1.69 kg, and birth weight >1.48 kg are suitable for treatment with aminophylline. Monitoring of serum theophylline concentration should be implemented in the absence of clinical response or in case of suspected adverse reactions. Key Words: aminophylline, apnea of prematurity, concentration, efficacy, factor